IMPLEMENTASI KEIKHLASAN DAN KEDISIPLINAN DALAM PENDIDIKAN AGAMA BERBASIS NILAI - Muhammad Uchaida Sabilil Matin (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2026)
This study aims to analyze the practice of sincerity, discipline, and educational leadership in the Qur’anic learning activities led by Bapak Ali Ahsan in Dukuh Tanggulangin, Jati Wetan Village, Jati District, Kudus Regency. Community-based religious education plays a strategic role in shaping character, morality, and religious culture within society. This research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using interactive data analysis techniques, including data reduction, data display, and conclusion drawing. The findings reveal that teacher sincerity serves as the primary foundation for building emotional bonds with students, discipline is implemented through role modeling and habituation, and value-based leadership contributes significantly to character formation and community participation. The educational practices not only improve students’ Qur’anic literacy but also foster responsibility and social solidarity. Therefore, community-based religious education represents a relevant model for educational and social development in contemporary contexts.